Runtime verification : 16th International Conference, RV 2016, Madrid, Spain, September 23-30, 2016, Proceedings /: 16th International Conference, RV 2016, Madrid, Spain, September 23-30, 2016, Proceedings. (2016) - Unknown
No abstract available